VALUE OF WORK ETHIC IN PAPPASENG BUGIS AND ITS IMPLICATIONS FOR STUDENT CAREER MATURITY DURING THE COVID-19 PANDEMIC : (STUDY OF GADAMERIAN HERMENEUTICS) - M Yunus Sudirman (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2021)
Bugis people's way of life in working is guided by pappaseng. The purpose of this study is to describe the value of work spirit in pappaseng that students can guide in developing their career maturity towards guidance materials, especially during the COVID-19 pandemic. The research uses a qualitative approach; the type of hermeneutics is Gadamerian. They are collecting data using pappaseng text, interviews, and observations. Data analysis consists of (a) part, (b) whole, and (c) understanding of the underlying meaning. The findings of the work value research consist of ati mapaccing (good nature), lempu (honest), amaccang (intelligent), reso (hard work), sibaliperri (helping each other), and siri' (self-respect). Pappaseng work values ​​become a reference for the construction of career guidance materials to develop career maturity.